2000
DOI: 10.1351/pac200072010189
|View full text |Cite
|
Sign up to set email alerts
|

Photophysics and spectroscopy of metal particles

Abstract: This paper describes our recent work using ultrafast laser spectroscopy to examine the fundamental properties of metal particles. Two studies are presented. First, the characteristic time scale for electron-phonon coupling in Au particles with sizes between 2 and 120 nm has been examined by bleach recovery measurements. These experiments show that the coupling between the electrons and phonons is independent of particle size, to within the signal-tonoise of our experiments. We have also used transient absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…The recovery of the plasmon band on the picosecond timescale arises from the electron-phonon and phonon-phonon relaxation. Similar transient bleaching has also been observed for silver nanoparticles [66,73] and bimetallic particles [74][75][76]. The bleaching recovery of the pristine Au colloids consists of a fast (t ¼ 2:5 ps) and a slow process (t > 50 ps) [71].…”
Section: Photoinduced Transformations Of Metal Nanoparticlessupporting
confidence: 66%
“…The recovery of the plasmon band on the picosecond timescale arises from the electron-phonon and phonon-phonon relaxation. Similar transient bleaching has also been observed for silver nanoparticles [66,73] and bimetallic particles [74][75][76]. The bleaching recovery of the pristine Au colloids consists of a fast (t ¼ 2:5 ps) and a slow process (t > 50 ps) [71].…”
Section: Photoinduced Transformations Of Metal Nanoparticlessupporting
confidence: 66%
“…Ultrafast electron dynamics measurements using pump-probe techniques have shown that excited electrons in metal nanoparticles thermalize very fast (within 500 fs) to a hot Fermi distribution followed by electron cooling via electron-phonon collisions ($1 ps) and slower cooling of the nanoparticle lattice via phonon-phonon coupling ($100 ps) [2,41,[78][79][80][81]. The hot-electron cooling rate in gold nanoparticles has been found to be $1 ps and is unaffected by changes in the size or shape of the nanoparticles [41].…”
Section: Influence Of Coupling and Near-field On Electron Relaxationmentioning
confidence: 99%
“…In Situ Measurements of the Particle Size Distribution. The successful use of time-resolved spectroscopy to analyze thin films suggests that our experiments might be useful for measuring particle size distributions . In fact, there are several advantages of these experiments compared to TEM or STM measurements.…”
Section: Coherent Excitation Of Acoustic Phonon Modesmentioning
confidence: 99%